Fenomena Penggunaan Model Pembelajaran Konstektual terhadap Peningkatan Kemampuan Menulis Cerpen di MTS ISTIQLAL Jakarta - Largo Gibran Khan; Damanhuri Damanhuri; Een Nurhasanah (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
Many students find it difficult to express ideas into a complete story. Their imagination often stops halfway due to limited vocabulary, lack of understanding of story structure, and minimal practice in creative writing. The purpose of this research is to describe the profile of contextual learning on the ability to write short stories at MTs Istiqlal Jakarta, to examine the impact before the use of the contextual learning model on the ability to write short stories at MTs Istiqlal Jakarta, to examine the impact after the use of the contextual learning model on the ability to write short stories at MTs Istiqlal Jakarta, and to describe the effect of learning modules on the ability to write short stories of seventh-grade students at MTs Istiqlal Jakarta. This research uses a quantitative approach with an experimental method. The type of research used is One Group Pretest-Posttest Design, namely a design that only involves one experimental group. The sample in this study consists of 25 (twenty-five students) of grade VII MTs Istiqlal Jakarta. The results of the research show that learning at MTs Istiqlal Jakarta is still dominated by the lecture method so students tend to be passive and their short story writing ability is relatively low, especially in finding ideas, developing plot, and building characters. The implementation of the contextual learning model has been proven to significantly improve students' short story writing ability through active involvement, linking material with real experiences, idea exploration, collaboration in learning communities, reflection, and more in-depth authentic assessment.